The role of psychological and medical variables in the process of adaptation to life with chronic illness in a group of COPD outpatients. Issue 10 (26th November 2019) - Wytrychiewicz, Kinga; Pankowski, Daniel; Bargiel-Matusiewicz, Kamilla; Dąbrowski, Jacek; Fal, Andrzej M.
ABSTRACT: Many studies suggest that psychological factors play an important role in chronic diseases. This study aimed to describe the role of certain medical variables (airflow obstruction indicators), personal resources, coping strategies, and health-related quality of life (HRQoL) in the process of adaptation to chronic obstructive pulmonary disease (COPD). The Brief COPE inventory, the General Self-Efficacy Scale, COPD Assessment Test, and the Acceptance of Life with the Disease Scale were completed by 111 outpatients. Groups of patients distinguished based on degree of airflow obstruction did not differ in frequency of use of coping strategies, General Self-efficacy, HRQoL, or level of acceptance of life with the disease. Groups distinguished in terms of frequency of the strategies used differed in terms of indicators of airflow obstruction and acceptance of life with the disease. General Self-efficacy was correlated with active coping, use of emotional support, and planning. The best predictors of Acceptance of Life with the Disease were coping strategies, HRQoL, and General Self-efficacy. The obtained data indicated that psychological factors play an important role in adapting to life with illness. This study also found that self-efficacy is a very significant personal resource which future psychological interventions for COPD could focus on.